2018
DOI: 10.31234/osf.io/5ueh7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Event structures drive semantic structural priming, not thematic roles: Evidence from idioms and light verbs

Abstract: What are the semantic representations that underlie language production? We use structural priming to distinguish between two competing theories. Thematic roles define semantic structure in terms of atomic units that specify event participants and are ordered with respect to each other through a hierarchy of roles. Event structures instead instantiate semantic structure as embedded sub-predicates that impose an order on verbal arguments based on their relative positioning in these embeddings. Across two experi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Studies of adult sentence processing have shown that adults activate information about recipients and goals upon hearing verbs that encode these participants (e.g., teach activates recipient, enter activates goal) (Andreu, Sanz-Torrent, & Rodríguez-Ferreiro, 2016; Boland, 2005). More importantly, priming studies with adults show the order of thematic roles can be primed independently of syntactic structure, indicating abstract knowledge of a Goal category (Chang, Bock, & Goldberg, 2003; Ziegler & Snedeker, 2018) and a Recipient category (Cai, Pickering, & Branigan, 2012; Cho-Reyes, Mack, & Thompson, 2016; Hare & Goldberg, 1999; Köhne, Pickering, & Branigan, 2014; Pappert & Pechmann, 2014; Salamoura & Williams, 2007; Ziegler, Snedeker, & Wittenberg, 2018), categories that transcend verb-specific knowledge. For example, Chang et al (2003) found that English speakers were more likely to produce sentences where the goal was mentioned in the second position after the verb (e.g., the farmer heaped straw onto the wagon ) when primed by a sentence with the same thematic order (e.g., the maid rubbed polished onto the table ) than a prime sentence where the goal was in the first position (e.g., the maid rubbed the table with polish ).…”
Section: Recipients Goals and Sourcesmentioning
confidence: 99%
“…Studies of adult sentence processing have shown that adults activate information about recipients and goals upon hearing verbs that encode these participants (e.g., teach activates recipient, enter activates goal) (Andreu, Sanz-Torrent, & Rodríguez-Ferreiro, 2016; Boland, 2005). More importantly, priming studies with adults show the order of thematic roles can be primed independently of syntactic structure, indicating abstract knowledge of a Goal category (Chang, Bock, & Goldberg, 2003; Ziegler & Snedeker, 2018) and a Recipient category (Cai, Pickering, & Branigan, 2012; Cho-Reyes, Mack, & Thompson, 2016; Hare & Goldberg, 1999; Köhne, Pickering, & Branigan, 2014; Pappert & Pechmann, 2014; Salamoura & Williams, 2007; Ziegler, Snedeker, & Wittenberg, 2018), categories that transcend verb-specific knowledge. For example, Chang et al (2003) found that English speakers were more likely to produce sentences where the goal was mentioned in the second position after the verb (e.g., the farmer heaped straw onto the wagon ) when primed by a sentence with the same thematic order (e.g., the maid rubbed polished onto the table ) than a prime sentence where the goal was in the first position (e.g., the maid rubbed the table with polish ).…”
Section: Recipients Goals and Sourcesmentioning
confidence: 99%
“…When these variables can be disentangled, however, there is evidence for multiple sources of priming. For example, Ziegler, Snedeker, and Wittenberg (2018) found priming from idiom ("The boss gives his employee the boot") and light verb primes ("The mother gives the child a scolding") to compositional dative targets, suggesting that syntactic structure can prime even when thematic differences are present. However, priming was enhanced from compositional dative primes ("The boy gives his classmate a pen") to other compositional dative targets ("The waitress gives the man a glass"), suggesting that thematic structure also primes (see also, e.g., Chang, Bock, & Goldberg, 2003;Hare & Goldberg, 1999;.…”
Section: Sources Of Dative Primingmentioning
confidence: 99%
“…Here we focus on collecting language production data. Although collecting spoken data through the internet is not new (Vogt et al 2021;Ziegler et al 2018), past studies typically rely on testing fixed participant pools and not on collecting community samples that are likely the target of research on understudied languages.…”
Section: Language Coverage Across Subdisciplinesmentioning
confidence: 99%